Classification, History, and Future Prospects of Maxillofacial Prosthesis - Fernanda Pereira de Caxias; Daniela Micheline dos Santos; Lisiane Cristina Bannwart; Clovis Lamartine de Moraes Melo Neto; Marcelo Coelho Goiato (International Journal of Dentistry)
This review presents a classification system for maxillofacial prostheses, while explaining its types. It also aims to describe their origin and development, currently available materials, and techniques, predicts the future requirements, and subsequently discusses its avenues for improvement as a restorative modality. A literature search of the PubMed/Medline database was performed. Articles that discussed the history, types, materials, fabrication techniques, clinical implications, and future expectations related to maxillofacial prostheses and reconstruction were included. Fifty-nine articles were included in this review. Maxillofacial prostheses were classified as restorative or complementary with subclassifications based on the prostheses finality. The origin of maxillofacial prostheses is unclear; however, fabrication techniques and materials have undergone several changes throughout history. Currently, silicones and acrylic resins are the most commonly used materials to fabricate customized prostheses. Maxillofacial prostheses not only restore several types of orofacial defects but also improve the patients’ quality of life. Although the current clinical scenario concerning the field of maxillofacial prostheses is promising, improvements in material quality and techniques for maxillofacial prostheses may be expected in the future, to produce better results in the treatment of patients.